Ultrasonography Evaluation of Patency of Implanted Infra-Renal Vascular Grafts in the Rat Model. - Da Silva, Natercia (Division of Cardiothoracic Surgery, 2021)
Introduction: Intensive research over the last six decades has resulted in minimal improvement in vascular graft development. Small animal models are the first line of species exposed to vascular graft implantation and invasive monitoring of experimental graft patency may contribute to pain, suffering, higher cost and earlier sacrifice. Non-invasive ultrasonographic evaluation of vascular implants during the conduction of animal studies allows for chronic follow-up with multiple assessments. This study aims to apply and endorse the utilization of ultrasound as a less invasive diagnostic method in determining patency of vascular grafts in units where imaging modalities like Computerized Tomography (CT) and Magnetic Resonance Imaging (MRI) are not readily available. Methods: Pre-operative control ultrasound evaluation of the ejection fraction, aortic diameter and aortic velocity were conducted on Wistar rats (250-350g). Infra-renal aortic vascular graft implantation was then performed, with 8 rats receiving straight (1.8mm ID, 18mm length) expanded polytetrafluoroethylene (ePTFE) grafts, while 12 rats received a long (1.8mm ID, 100mm length) looped ePTFE conduit with a sealed mid-graft (10mm length) section. Ultrasonography was conducted on days 1, 3, 7 and weeks 4, 8 and 12 post operatively. Grafts were explanted if there was any ultrasonographic evidence of occlusion or at twelveweek termination of the study. Explant was preceded by angiography and followed by histological assessment of the grafts for patency. Results: Three of the looped and all 8 of the straight grafts were patent at the 12 week explant time point, as correctly assessed by ultrasound and confirmed by angiography and histology. Three of the nine occluded looped grafts were explanted at eight weeks due to early ultrasonographic detection of occlusion; the remaining 6 were explanted at twelve weeks. There were two false positive results, which were incorrectly assessed as patent at twelve weeks of implantation on ultrasonographic evaluation, but confirmed to be occluded on angiography at explant. The results of ultrasonography evaluation of implanted infra-renal vascular grafts had a high specificity of 100% with a sensitivity of 78%. The outcome of the results between ultrasound and angiography corresponded in 18 out of 20 vascular grafts, with a calculated positive predictive value (PPV) of 100% and a negative predictive value (NPV) of 85%. 4 Conclusion: Ultrasound is easily available and a non-invasive diagnostic modality allowing for safe and reliable results, which may be repeated at different time frames following vascular implants in small animal models. Ultrasonographic limitations exist, emphasizing the need for an experienced operator with adequate knowledge and training. Its use may be complicated by tortuous geometries of vessels, which is technically more challenging to evaluate with ultrasound than with imaging techniques like CT and MRI. It does, however, add information without additional loss of life or increased use of animal numbers. Ultrasound is an essential additive diagnostic tool for chronic follow-up and evaluation of vascular graft implants.